Potential of Purple Sweet Potato (Ipomoea batatas var. Ayamurasaki) Skin Extract Cream Preparation as an Antibacterial Against the Growth Activity of Propionibacterium acnes - Andi Indrawati; Suherman Baharuddin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the potential of a purple sweet potato (Ipomoea batatas var. Ayamurasaki) skin extract cream preparation on the growth activity of Propionibacterium acnes and determine the most effective concentration of the cream preparation. This type of research is experimental, namely laboratory research. Extraction process sample deusing the maceration method, the extract is made in the form of a cream dosage, next the growth activity of Propionibacterium acnes was tested. The research results show that cream preparations purple sweet potato (Ipomoea batatas var. Ayamurasaki) skin extract potentially hindering growth of Propionibacterium acnes, and the concentration of the cream preparation that is most effective in inhibiting growth Propionibacterium acnes is a concentration of 3% (FIV) with a Sig value. 0.000<0.05 (Oneway Anova α=0.05) in bacterial inhibition in the strong category (10–20 mm)